124k views
1 vote
Solve this and help me plsss​

Solve this and help me plsss​-example-1
User Jayesh
by
5.3k points

1 Answer

3 votes

Answer:

x = 2

Explanation:

(x² logₓ27) log₉x = x + 4

Use change of base formula.

x² (log 27 / log x) (log x / log 9) = x + 4

Simplify.

x² (log 27 / log 9) = x + 4

x² (log 3³ / log 3²) = x + 4

x² (3 log 3 / (2 log 3)) = x + 4

x² (3 / 2) = x + 4

3x² = 2x + 8

3x² − 2x − 8 = 0

(x − 2) (3x + 4) = 0

x = 2 or -4/3

Since x > 0, x = 2.

User Artyom Kiriliyk
by
5.7k points